Criminal Liability for Misuse of Electronic Medical Records in Health Services - Prilian Cahyani; Astutik Astutik (SOEPRA, 2019)
Electronic medical records (RME) have been used in hospitals as a substitute for or complementary to medical records in the form of paper. The obligation to make medical records is the responsibility of every doctor or dentist in carrying out the medical practice. However, the use of electronic-based medical records does not rule out the possibility of raising problems in the field of law, if some abuse it. This will raise the issue of who has the obligation to take responsibility. The problem is the background of the author to write in an article with the title "Accountability for the Misuse of Electronic Medical Record Abuse in Health Services". The formulation of the problem in this article is: 1) Setting an electronic medical record; 2) Criminal liability for the misuse of electronic medical records. The research method used is normative legal research with a statutory approach and a conceptual approach. From the discussion, it can be seen that in Indonesia the obligation to make medical records is specifically regulated in the Medical Practice Law. Furthermore, in the Ministry of Health No. 269 / MENKES / PER / III / 2008 especially Article 2 paragraph 2 states that medical records can be made electronically. However, to date, no specific regulations are governing electronic medical records. The use of electronic systems in medical records makes it necessary to heed the provisions of Law No. 11 of 2008 concerning Electronic Information and Transactions. The party who has the responsibility for the misuse of the Electronic Medical Record covers people who in this case are medical personnel or certain health workers. Hospitals can also be held responsible for the misuse of electronic medical records.